MicroRNA in regenerative medicine - Sen, Chandan K. (Academic Press, 2022)
Regulating virtually all biological processes, the genome's 2,654 newly discovered variants of mature microRNAs - short ribonucleic acid molecules found in eukaryotic cells - hold a key role in the body's toolkit of regenerative and reparative capacities. Identifying how to activate and deliver these specialist molecules may aid in the repair and regeneration of major tissue and organ damage in future therapies. In MicroRNA and Regenerative Medicine, Second Edition, over 50 leading experts address foundational and emerging topics in the field. Concisely summarizing and evaluating key findings from new research and their translational application, contributors examine current and future significance of clinical research in the miRNA area. Coverage encompasses all major aspects of fundamental stem cell and developmental biology, including the uses of miRNA in cell and tissue plasticity, developmental biology, tissue repair, and regeneration. In particular, contributors provide focused coverage of methodologies for regenerative intervention and tissue engineering. Topics new to this edition include proteomic changes during tissue repair and regeneration, horizontal transfer of miRNAs in tissue regeneration, tissue stemness, peripheral nerve regeneration, miRNA as biomarkers, microRNA in pregnancy and embryo development, exogenous and diet derived microRNA in tissue development, ocular microRNA, mitochondrial microRNA, sensory hair cell death and regeneration, and microRNA in senescence.